PROTOTIPE INTEGRASI DATA MORBIDITAS PASIEN PUSKESMAS KEDALAM DATA WAREHOUSE DI DINAS KESEHATAN KABUTEN BANTUL - Totok Suprawoto; Enny Itje Sela; Syamsu Windarti (Jurnal TAM (Technology Acceptance Model), 2016)
Bantul District Health Office (DHO Bantul) is one of the agencies that are currently having problems to obtain health information that is accurate and current. The report should be made regularly by the health center then recapitulated in Bantul Health Office is a statement of outpatient morbidity such as Integrated Disease Surveillance (STP) report, a report based on the type of disease and others. The increasing number and complexity of morbidity data in Bantul Health Office environment, as well as the importance of planning and decision making, it is necessary to analyze and design data further using the data warehouse. From the analysis and design of data warehouse based on the fact constellation schema that includes dimensions: time, patient, age, disease and health centers, can then be further analyzed for purposes of making decisions using data mining. Furthermore, it can also be used to analyze patient data from multiple dimensions (time, patient, age, disease and health centers), and to analyze the growing number of patients from each period of benefit to the management of Bantul Health Office.